Determination of the Effective Charge Numbers and Ionic Mobilities of Single Isomer and Randomly Highly Sulfated Cyclodextrins by Capillary Isotachophoresis and Zone Electrophoresis - Šolínová, Veronika; Koval, Dušan; Kašička, Václav (Electrophoresis, 2025)
Sulfated cyclodextrins (CDs) are multiply negatively charged molecules widely used as chiral selectors in capillary electrophoresis (CE). In some of their applications, the effective charge numbers of their molecules were observed to be lower than the numbers of the attached sulfated groups due to strong binding of counterions. However, degree of reduction of the theoretical charge was not quantified. For that reason, in this study, capillary isotachophoresis (CITP) and capillary zone electrophoresis (CZE) were applied for the determination of the effective charge numbers and actual ionic mobilities of two kinds of sulfated CDs: single isomer sulfated α-, β-, and γ-CDs (SI-CDs) and randomly highly sulfated α-, β-, and γ-CDs (HS-CDs). The effective charge numbers of the SI-CDs and HS-CDs were determined from the length of their ITP zones, the ionic mobilities determined by CZE, and molar concentrations of their solutions applied for CITP analysis, and from the same parameters of reference compounds, formic acid for SI-CDs and dichloroacetic acid for HS-CDs. The determined effective charge numbers of the SI-CDs were equal to or only slightly lower than the numbers of sulfate groups in their molecules but the effective charge numbers of randomly HS-CDs were significantly (22.2%-27.8%) reduced as compared to the average numbers of sulfate groups in their molecules. In accordance with a lower number of sulfate groups in SI-CDs than in HS-CDs, the absolute values of the actual ionic mobilities of SI-CDs (35.5-37.5) × 10-9 m2 V-1 s-1 were lower than those of HS-CDs (43.5-44.1) × 10-9 m2 V-1 s-1.
Keywords: counterion condensation; Isotachophoresis; izotachoforéza; sírany; elektroforéza kapilární; Electrophoresis, Capillary; isomerie; Cyclodextrins; Sulfates; Stereoisomerism; capillary isotachophoresis; capillary zone electrophoresis; stereoizomerie; effective charge; cyklodextriny; Isomerism; charge number